Pengembangan Asessment Higher Order Thinking Skills (HOTS) Berbasis Computer Based Test (CBT) pada Mata Kuliah Prinsip Pengajaran dan Asesmen yang Efektif - Mgs Tibrani; Kodri Madang; Nike Anggraini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The aim of this research is to produce a Higher Order Thinking Skills (HOTS) assessment product based on a Computer Based Test (CBT) with three types of HOTS questions (true or false, multiple choice, and fill in the blank and matching) based on the factual knowledge dimension, conceptual, procedural, and metacognitive with illustrations in the form of discourse, images, graphics, videos, animations, and interactive stimulation, as well as providing feedback after going through the logical validation, empirical validation, and respondent questionnaire stages. The CBT-based HOTS assessment product was implemented for PPG students, Faculty of Teacher Training and Education, Sriwijaya University in the Principles of Effective Teaching and Assessment course with R&D research steps. The product trial subjects in this research were limited to a small scale, namely 8 PPG Pre-Service Biology Education Study Program students, FKIP, Sriwijaya University. The technique for selecting product trial subjects in this research is the cluster sampling technique, namely a sampling method based on certain clusters. The data collection technique uses expert validation sheets and respondent questionnaires, then the data collected is analyzed quantitatively descriptively. Data obtained from questionnaires and scientific communication skills were analyzed using a rating scale. To analyze each statement or indicator, the frequency of answers for each category (answer choices) is calculated and added up. The development of HOTS questions based on the Computer Based Test in the Principles of Effective Teaching and Assessment course is based on two validation values from the validator, namely 81%, meaning that the material and language that has been designed by the researcher is valid and suitable for use. Apart from that, HOTS test questions are said to be practical if the score on the practicality criteria is at least 75%. Based on the results of the student response questionnaire, a score of 91.81% was obtained.